42.3k views
4 votes
What is the following product? RootIndex 3 StartRoot 16 x Superscript 7 Baseline EndRoot times RootIndex 3 StartRoot 12 x Superscript 9 Baseline EndRoot x squared (RootIndex 3 StartRoot 28 x squared EndRoot) x Superscript 5 Baseline (RootIndex 3 StartRoot 28 x EndRoot) 4 x squared (RootIndex 3 StartRoot 3 x squared EndRoot) 4 x Superscript 5 Baseline (RootIndex 3 StartRoot 3 x EndRoot)

2 Answers

4 votes

Answer:

D (4x^5(3sqrt3x)

Explanation:

User Valera Shutylev
by
5.0k points
3 votes

Answer:


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)\sqrt[3]{3x} }

Explanation:

Given


\sqrt[3]{16x^7} * \sqrt[3]{12x^9}

Required

Find the products

From laws of indices;


\sqrt[m]{a} * \sqrt[m]{b} = \sqrt[m]{a*b}

So;


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{16x^7 * 12x^9}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{16* x^7 * 12 * x^9}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{16*12* x^7 * x^9}

From laws of indices


a^m * a^n = a^(m+n); So,


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{16*12* x^(7+9)}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{16*12* x^(16)}

Expand 16 * 12


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{4*4*4*3* x^(16)}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = \sqrt[3]{4^3 *3* x^(16)}

From laws of imdices


a^{(1)/(m)} = \sqrt[m]{a}

So;


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4^3 *3* x^(16)})^{(1)/(3)}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4^{3*{(1)/(3)}} *3^{{(1)/(3)}}* x^{16*{(1)/(3)}}})


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 *3^{{(1)/(3)}}* x^{(16)/(3)}}

Divide 16 by 3 (Write as ,mixed number)


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 *3^{{(1)/(3)}}* x^{5(1)/(3)}}

Split mixed numbers


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 *3^{{(1)/(3)}}* x^{5+(1)/(3)}}

Apply law of indices


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 *3^{{(1)/(3)}}* x^(5)*{x ^(1)/(3)}}

Reorder


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 * x^(5)*3^{{(1)/(3)}}*{x ^(1)/(3)}}


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)*3^{{(1)/(3)}}*{x ^(1)/(3)}}

Apply law of indices


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)*\sqrt[3]{3} *\sqrt[3]{x} }


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)*\sqrt[3]{3*x} }


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)*\sqrt[3]{3x} }


\sqrt[3]{16x^7} * \sqrt[3]{12x^9} = {4 x^(5)\sqrt[3]{3x} }

User Persimmonium
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.